Integrating Islamic Marketing Education to Building Consumer Literacy and Entrepreneurial Mindset in Pesantren - Harisandi, Prasetyo; Hurriyati, Ratih; Yuliawati, Tia; Ramadhani, Indi; Maulana, Yono; Yusriani, Sri; Imran, Muh. Erwinto (Jurnal Pendidikan Islam, 2026)
Globally, Islamic educational institutions face increasing pressure to respond to digital economic transformations while maintaining Islamic ethical and pedagogical foundations. This study aims to examine the role of Islamic Marketing Education (IME), integrated with the Unified Theory of Acceptance and Use of Technology (UTAUT), in enhancing consumer literacy and fostering an entrepreneurial mindset among santri in Indonesian Islamic boarding schools (pesantren). Using a quantitative cross-sectional survey design, data were collected from 350 santri and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS version 4. The results demonstrate that IME has a positive and significant effect on consumer literacy, entrepreneurial mindset, and core UTAUT constructs, including performance expectancy, effort expectancy, social influence, and facilitating conditions. In addition, entrepreneurial mindset and UTAUT variables significantly predict santri’ intention to use e-commerce, while consumer literacy acts as a moderating factor that supports reflective, value-based decision-making and mitigates uncritical technology adoption. The study concludes that integrating Islamic pedagogical approaches with technology acceptance frameworks effectively strengthens digital readiness without compromising Islamic moral principles. These findings imply that Islamic education, particularly within pesantren contexts, should systematically incorporate ethically grounded digital entrepreneurship and consumer literacy to prepare students for responsible participation in the contemporary digital economy.